PENGARUH BRAND IMAGE DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN SAFF & CO. DI KUPANG - Radhiya Esa Fitriawati; Siti Aminah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to examine how brand perception and electronic word-of-mouth (E-WOM) affect Kupang consumers' decisions to buy SAFF & Co. products. An associative quantitative methodology is employed in the study, and 88 respondents were chosen for the sample using convenience sampling methods. SEM-PLS was used for data analysis after closed questionnaires were used to gather data. The findings demonstrated that E-WOM and brand perception had a strong and favorable impact on consumer decisions. Positive word-of-mouth (E-WOM) from customer reviews impacts consumer purchase decisions, while a good company image boosts consumer trust. To sum up, keeping up a positive internet presence and brand reputation is critical to boosting sales. This study suggests that future research should include more factors and a larger sample size.